Maintenance chemotherapy in biliary tract tumours in the era of immuno-chemotherapy - A. Lamarca; J. Adeva; I. Ales Díaz; R. Alvarez Gallego; A.J. Muñoz Martín; T. Macarulla Mercade (ESMO Gastrointestinal Oncology)
Biliary tract tumours (BTCs) are malignancies with a poor prognosis. Regarding first-line therapy options, cisplatin and gemcitabine (CisGem) alone has been the standard therapy option for more than a decade. This has changed recently, due to the incorporation of immunotherapy into this combo, with latest studies showing how the addition of immunotherapy with either durvalumab or pembrolizumab can improve patients’ outcomes. However, the adequate duration of CisGem in advanced BTCs has remained an open debate. We provide a detailed summary and discussion on current evidence in terms of adequate duration of chemotherapy in the immuno-chemotherapy era, with the aim of informing best practice. Based on the data available and summarised here, the differences are small and individual decisions should be pursued for the sake of not compromising the bone marrow reserve for delivering second-line therapies. In the era of immuno-chemotherapy, maintenance chemotherapy seems to be of very limited benefit and maintenance with the checkpoint inhibitors being utilised seems sufficient. For patients being treated with chemotherapy alone, maintenance chemotherapy should also be carefully considered and decisions individualised.